Najmuddin An-Nasafi and his Concept in the Imam question - Zhamashev, A.; Kurmanaliyeva, A.; Nauryzaliyev, I. (Eurasian Journal of Religious Studies, 2022)
This article provides information about the life and work of Abu Hafs Omar ibn Muhammad ibn Ahmad ibn Luqman al-Nasafi, a well-known scientist, historian and author of many biographical and historical works. And also briefly analyzed biographical and reliable data about his life and about his teachers and students. The titles and main themes of a number of his significant works in the field of tafsir, kalam, fiqh and hadith are considered, and briefly analyzed by referring to historical and biographical works. The article mentions a short four-page treatise that was based on the Hanafi doctrine of the famous work of the scholar, "al-Aqida al-Nasafiya", which contributed to the widespread popularization of the teachings of Maturidi in Muslim countries where issues related to Imamism are discussed. The article also discusses the conditions under which Muslims must have an imam (leader) to implement their rules and laws, and the requirements for the position of imam. The main focus is on the fact that the imam must have sufficient knowledge, abilities, courage in the execution of laws, the implementation of criminal penalties, the opposition to enemies and the protection of the rights of citizens living in the territory of the muslim state.Key words: Najmuddin an-Nasafi, Imam, Caliphate, Imamship, Madhhab Imamia.
Keywords: Najmuddin an-Nasafi; Imam; Caliphate; Imamship; Madhhab Imamia